Enhancement Of Yield, Starch, And Amylose Content Of Two Indonesian Cassava Genotypes By Producing Gamma Irradiated-Induced Mutants - Enny Sudarmonowati; N Sri Hartati; Supatmi Supatmi (ANNALES BOGORIENSES, 2020)
As an important carbohydrate-source food crop and raw materials of starch-based industries,  accelerated cassava breeding has been extensively pursued through various procedures, among others, is mutant induction using gamma irradiation combined with molecular marker. Iding, a local genotype cassava has been compared with a national variety Adira 4 for its yield attributes following gamma irradiation at various dose levels ( 2, 20, 30, and 50 krad). The mutation rate was conducted based on morphological characteristics and identification using RAPD by employing random primer OPB-10. Evaluation was conducted on mutant lines producing high potential yield,  high starch and amylose contents. The fourth generation of irradiated Adira 4 (2 and 30 krad) and Iding (2 krad) exhibited higher yield and amylose content as compared to their representative controls. The yield of 30 krad irradiated Adira 4 indicated by mean tuber weight per individual could reach more than twice of that of control and almost 1.5 times of that irradiated with 2 krad. The levels of amylose content of all irradiated ones, regardless of genotypes and gamma irradiation doses  (2 and 30 krad) were higher than that of control. In most parameters, irradiated Adira 4 was superior to irradiated Iding.